A STUDY ON OPTIMIZING THE TECHNICAL TRAINING OF THE REPRESENTATIVE RUGBY TAG - Corduneanu Marius Lucian; Leuciuc Florin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2021)
Sports games enjoy a great spread and popularity from an early age, which has determined the continuous progress of the theory of Physical Education, the evolution of its teaching methodology and an increase in technical training performances of the representative school teams. I chose this research topic because the school where I am a teacher has only one class per level in secondary school, and the sports game that allowed me to engage as many students (both girls and boys) is the game of rugby. Therefore, because the material base of the school allows me, I introduced the rugby tag game in my annual planning, and I used this game at each class, even forming a representative school team, to the delight of my students. According to the results and statistical analysis, the students in the experiment group have visibly progressed in the final test compared to the initial one. As a proposal, I would urge that the technical-tactical training of the students from the representative school rugby-tag team do not represent a finality but it must be constantly combined with the physical, mental and biological side of the training.